Implementasi Sistem Monitoring Lingkungan Pada Budidaya Tanaman Hidroponik Berbasis IoT - Pratama, Ariski; Styawati, Styawati; Samsugi, Selamet; Alim, Syahirul (Politeknik Harapan Bersama, 2024)
The increase in population and the reduction of agricultural land are major concerns in Indonesia. The country's population rose from 244,016,173 in 2010 to 277,534,122 in 2023, raising food needs. Population growth promotes the use of pesticides to protect agriculture;ntegration of hydroponic automation technology in households with limited land, such as for salad and sawmills, is expected to meet increasing food needs, reduce environmental impact, and improve well-being, in line with the SDGs. however,excessive use can lead to environmental damage, water pollution, and health risks for humans. In addressing this problem, hydroponic planting media became a potential solution. Hydroponics is the cultivation of plants without soil, using a nutrient solution. This technology supports the Sustainable Development Goals (SDGs) with clean and sustainable crop growth. Integration of hydroponic automation technology for households with limited land, such as for salad and sawmills, is expected to meet increasing food needs, reduce environmental impact, and improve well-being, in line with the SDGs. Thus, hydroponics can be an effective solution in addressing the agricultural challenges facing Indonesia